1967
DOI: 10.1111/j.1365-2672.1967.tb00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology of Prepacked Pork with Reference to the Gas Composition within the Pack

Abstract: Bncteriological changes in pork stored a t 16 and 2" under gas permeable and gas impermeable films and 'aerobic' conditions have been studied. The concentrations of CO,, 0, and N, in the atmosphere within the packs were also determined. The groups of bacteria isolated from prepaclred pork were Pseudomonas-Achronaobacter spp., Rzuthia spp., Microbacterium thermosphactum, Enterobacter-Hafnia spp. and lactobacilli. Their importance is discussed in relation t,o storage temperature and gas composition within the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 13 publications
1
27
0
1
Order By: Relevance
“…The initial pH of the sample was 6.33 ± 0.02 when collected from the slaughterer. In aerobic spoilage at refrigerated conditions, Pseudomonas is the major microorganism of interest 19,20 and it is inhibited at higher O 2 levels. 21 Thus, this could be the reason for lower TVBN at 45% and 55% O 2 .…”
Section: Measurement Of Raw Meat Used For Packagingmentioning
confidence: 99%
“…The initial pH of the sample was 6.33 ± 0.02 when collected from the slaughterer. In aerobic spoilage at refrigerated conditions, Pseudomonas is the major microorganism of interest 19,20 and it is inhibited at higher O 2 levels. 21 Thus, this could be the reason for lower TVBN at 45% and 55% O 2 .…”
Section: Measurement Of Raw Meat Used For Packagingmentioning
confidence: 99%
“…For example, it has been reported that CO2 had little effect on the facultative anaerobe EnterobacterHafnia spp. and B. thermosphactum (Gardner et al, 1967). noted that B. thermosphacta on beef increased at the same rate as total counts in air, vacuum, and in a 20%C02/2%02/78%N2 mixture.…”
Section: Moraxella -Acinetobacter Groupmentioning
confidence: 91%
“…Pseudomonas-Achromobacter spp. and other related psychrotrophs which grow rapidly and produce off-odors and flavors in raw meats are selectively inhibited by CO2 (Gardner et al, 1967;.…”
Section: Moraxella -Acinetobacter Groupmentioning
confidence: 99%
See 2 more Smart Citations